Comprehensive Evaluation Of The Bachelor Of Teaching Arabic Curriculum Based On Academic Standards At Al-Madinah International University - Ayman Aied Mohammed Mamdouh; Amal Mahmoud Ali; Najwa Gareeb Ali (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aimed to evaluate the alignment of the Bachelor of Teaching Arabic program at Al-Madinah International University with national and international academic standards across four key domains: curriculum content, teaching methods, assessment practices, and learning outcomes. A quantitative descriptive research design was employed, using a structured questionnaire administered to ten purposively selected academic staff members involved in the program. The instrument consisted of 32 items rated on a 5-point Likert scale, and its internal consistency was confirmed with a Cronbach’s Alpha of 0.87. Descriptive statistics revealed high levels of alignment in three domains: curriculum content (M = 4.21, SD = 0.45), teaching methods (M = 4.08, SD = 0.52), and learning outcomes (M = 4.13, SD = 0.48). Assessment and evaluation practices showed a slightly lower level of alignment (M = 3.94, SD = 0.60). One-Way ANOVA results indicated no statistically significant differences based on academic rank in the domains of curriculum content (F = 1.24, p = 0.29), teaching methods (F = 0.88, p = 0.42), and learning outcomes (F = 1.57, p = 0.21). However, a statistically significant difference was found in perceptions of assessment practices (F = 3.67, p = 0.04), suggesting variation across faculty ranks. The findings highlight the program’s strong curriculum foundation and effective instructional practices, while pointing to the need for greater consistency in assessment approaches. Recommendations include standardizing evaluation tools, enhancing faculty training, and strengthening collaborative curriculum review processes to support continuous improvement. The study contributes valuable data for curriculum developers and policymakers aiming to enhance quality assurance in Arabic teacher education.